2011
DOI: 10.1007/s00418-011-0868-1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of BrdU label-retaining dental pulp cells to allogenic tooth transplantation into mouse maxilla

Abstract: Recently, we demonstrated that a pulse of BrdU given to prenatal animals reveals the existence of slow-cycling long-term label-retaining cells (LRCs), putative adult stem or progenitor cells, which reside in the dental pulp. This study aims to clarify responses of LRCs to allogenic tooth transplantation into mouse maxilla using prenatal BrdU-labeling, in situ hybridization for osteopontin and periostin, and immunohistochemistry for BrdU, nestin, and osteopontin. The upper-right first molars were allografted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
0
11
1
1
Order By: Relevance
“…The differentiation capacity of LRCs in mice has been recently clarified after the exogenous stimuli such as allogenic tooth transplantation in our previous study: the LRCs in the transplant maintain Proliferating cells are shown in red, strong nestin-IR is shown in blue, weak nestin-IR is shown in light blue and dense LRCs are shown in green. Enamel knots in tooth germs are shown in yellow their proliferative and differentiation capacity for odontoblastlike cells (Mutoh et al 2011;Saito et al 2011). …”
Section: Mapping Of Lrcs In the Growing Toothmentioning
confidence: 99%
“…The differentiation capacity of LRCs in mice has been recently clarified after the exogenous stimuli such as allogenic tooth transplantation in our previous study: the LRCs in the transplant maintain Proliferating cells are shown in red, strong nestin-IR is shown in blue, weak nestin-IR is shown in light blue and dense LRCs are shown in green. Enamel knots in tooth germs are shown in yellow their proliferative and differentiation capacity for odontoblastlike cells (Mutoh et al 2011;Saito et al 2011). …”
Section: Mapping Of Lrcs In the Growing Toothmentioning
confidence: 99%
“…Therefore, the formation of mineralized tissue within the pulp cavity has been widely examined in both clinical and animal studies. These studies ordinarily focused on the formation of reparative dentin and the dentin bridge, although several other reports described the induction of bone-like tissues in the pulp cavity following various stimulations such as tooth transplantation (Hosoya et al 2003) or replantation (Zhao et al 2007;Mutoh et al 2011), traumatic injury (Robertson et al 1997), and laser irradiation (Tate et al 2006). These bone-like tissues are quite similar to normal bone regarding their histological appearance and matrix properties; however, the origin of the osteoblast-like cells that appear in the dental pulp is still controversial.…”
mentioning
confidence: 99%
“…Similarly, the M1 of a GFP transgenic mice or wild-type mice was transplanted into the alveolar socket of wild-type or GFP transgenic mice, respectively. With respect to BrdU-labeling, repeated intraperitoneal injections (E17-21) into pregnant Wistar rats have been demonstrated to successful identify dense slow-cycling long-term labelretaining cells (LRCs), which are regarded to be putative adult stem or progenitor cells (Ishikawa et al 2011;Mutoh et al 2011). These cells can be found in the mature tissue of born animals in the center of the dental pulp, associating with blood vessels.…”
Section: Cells/stem Cellsmentioning
confidence: 98%
“…To analyze the processes occurring after allogenic tooth transplantation into mouse maxilla, Mutoh et al 2011) made use of prenatal bromodeoxyuridine (BrdU)-labeled and GFP transgenic mice. In the case of the BrdU-labeled mice, the BrdU-labeled extracted molar (M1) was allo-grafted into the original socket of non-labeled, M1-extracted mice and vice versa.…”
Section: Cells/stem Cellsmentioning
confidence: 99%